Can the IMF's Medium-Term Growth Projections Be Improved? - Zalduendo, Juan (IMF Working Papers; Working Paper ;, 2004)
Numerous reports have noted that the IMF's medium-term growth projections are overly optimistic, raising questions as to how these can be improved. To this end, we estimate a growth model and examine its out-of-sample forecasting properties relative to those of IMF projections. The model's projections outperform those of the IMF in all regions and among most income groups-projections are less biased (one-quarter of the IMF bias) and have smaller standard errors (20 percent lower root mean squared errors) even after controlling for the IMF's macroeconomic assumptions. The paper does not attempt to address the criticisms that have been leveled against the empirical growth literature, but the results suggest that benefits can be derived from bringing systematic analysis to bear on cross-country information.